2015
DOI: 10.1002/pds.3778
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stevens-Johnson syndrome and toxic epidermal necrolysis in electronic health record databases

Abstract: Newer ICD-9 codes, along with length of hospitalization, identified patients with a high likelihood of SJS/TEN. This is important for identification of subjects for future pharmacogenomics studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Therefore, we limited our study to no earlier than 2009. Since the reclassification, the newer ICD‐9 codes used in this study have been shown to better reflect SJS and TEN cases than codes before 2008 …”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, we limited our study to no earlier than 2009. Since the reclassification, the newer ICD‐9 codes used in this study have been shown to better reflect SJS and TEN cases than codes before 2008 …”
Section: Methodsmentioning
confidence: 94%
“…Individuals younger than 18 years old admitted to one of the hospitals in the 2009 or 2012 KID database with a primary discharge diagnosis of 695.13 (SJS), 695.14 (SJS/TEN overlap syndrome), or 695.15 (TEN) and a LOS of longer than 3 days were included . Incorporating LOS can improve retrospective identification of SJS/TEN cases . A LOS of longer than 3 days was chosen based on previously published studies .…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previously validated algorithm, patients who had a LOS <3 days were excluded to improve positive predictive value of diagnostic codes 13 . Patients with a concomitant diagnosis of any other bullous dermatosis were excluded (ICD-9-CM: 694.0-694.9), since certain bullous dermatoses have rarely been reported to masquerade as TEN 14 .…”
Section: Exposures and Outcomesmentioning
confidence: 99%
“…Chart review was then performed to verify that the clinical symptoms were compatible with the coded diagnosis and to identify the specific agent most likely associated with the adverse reaction noted. 8 New C difficile infections within 90 days of delivery were identified by either a new report of C difficile coded (ICD-9 Code 008.45) or a positive microbiology culture or polymerase chain reaction for C difficile within 90 days of delivery.…”
Section: Original Research and Contributionsmentioning
confidence: 99%